The application of SCOR and DEMATEL models for assessing agricultural supply chain risks: a case study in the Mekong Delta (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Agricultural products are major contributors to economic growth and food security in Vietnam. In the Mekong Delta region, agricultural products offer developmental benefits, but not without risks and challenges. Thus, this study identified risks, impacts, and the importance of the agricultural supply chain (ASC) in the Mekong Delta. The study combined qualitative and quantitative methods to review relevant domestic and international literature for data retrieval. Subsequently, the SCOR model was used to identify ASC risk factors, whereas the DEMATEL model was adopted to determine the importance of the identified risks. A total of 17 existing ASC risks in the Mekong Delta were identified in this study. Among the risks, “Planning for production, transportation, and delivery”, “Loss of agricultural products due to damage and quality degradation” and “Non-standard goods” were the most significant concerns in this study. In contrast, the respondents were less concerned about risks such as “Shortage of skilled labour and lack of access to experts” and “Purchasing cultivation seeds”. Meanwhile, “Shortage of skilled labour and lack of access to experts” and “Damaged machinery, production, and vehicles” were the highest rated impacts in this study. Finally, “Increased operating costs” was the most significantly affected risk factor for the respondents. In conclusion, these findings serve as a foundation for deeper investigations studies in ACS, particularly in Vietnam.